2014
DOI: 10.4276/030802214x13990455043601
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Therapy for Care Home Residents with Stroke: What is Routine National Practice?

Abstract: Introduction: Information is currently lacking on the provision of occupational therapy for care home residents with stroke. The aim of this study was to identify current routine occupational therapy practice for this stroke population. Method: A questionnaire targeting qualified occupational therapists with work experience in a care home setting was designed, piloted, and transferred to an online survey. An invitation to participate was distributed via three of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
(10 reference statements)
2
4
0
Order By: Relevance
“…Crises notwithstanding, any reforms should prioritise quality of life for the duration of residents’ stays. We have found, as has previous research,3 that residents can lack access to, for example, specialist stroke therapies. There must be clarity for all regarding what homes can offer.…”
supporting
confidence: 85%
“…Crises notwithstanding, any reforms should prioritise quality of life for the duration of residents’ stays. We have found, as has previous research,3 that residents can lack access to, for example, specialist stroke therapies. There must be clarity for all regarding what homes can offer.…”
supporting
confidence: 85%
“…Goals were set most commonly to promote greater participation and independence in functional mobility, washing and dressing, and eating, which was in keeping with the main aims of the overall study intervention and also standard NHS occupational therapy practice in stroke rehabilitation (Steultjens et al, 2003). Few sessions involved addressing the facilitation of social activities, arranging discharge home and offering memory and cognition techniques, which is in keeping with findings from a national survey of routine occupational therapy conducted with residents with stroke living in a residential setting (Fletcher-Smith et al, 2014).…”
Section: Discussionsupporting
confidence: 54%
“…However, purposive sampling ensured sample characteristics were representative of the main trial intervention group. Furthermore, dependability of the results is increased as study findings are comparable to a much larger national review of routine occupational therapy for care home residents living with stroke, (Fletcher-Smith et al, 2014). Detailed information about the therapist's level of experience and specialism was not collected, therefore this limits the data, as it was not possible to compare different therapists.…”
Section: Discussionmentioning
confidence: 98%
“…Illuminating the scope and scale of the environmental work that therapists did within the care home setting complements other research, which highlights a commitment to interventions such as splinting and those targeting practicing of ADLs [30]. In addition, this theory area has demonstrated that making small changes to the environment could bring observable benefits for patients, which in turn enhanced therapists' commitment to the trial intervention.…”
Section: Discussionmentioning
confidence: 90%